2009
DOI: 10.1016/j.conengprac.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Two air path observers for turbocharged SI engines with VCT

Abstract: Nowadays, downsizing is a major way to reduce fuel consumption and pollutant emissions of Spark Ignition (SI) engines. In downsized engines, new air path management systems such as turbocharging or Variable Camshaft Timing (VCT) are including, and an efficient control of the air actuators is required for engine torque control. Two non-linear estimators are proposed to estimate non-measured variables of the air path. The first one is an incylinder air mass observer that combines feedforward neural static models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Volumetric efficiency is defined by Taylor [3] as the ratio of the mass of charge inducted into the cylinder to the mass of the charge mixture that would occupy the displaced piston volume at the inlet density. The determination of volumetric efficiency is critical to accurate charge estimation since it directly influences the speed–density charge mass calculation [1, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric efficiency is defined by Taylor [3] as the ratio of the mass of charge inducted into the cylinder to the mass of the charge mixture that would occupy the displaced piston volume at the inlet density. The determination of volumetric efficiency is critical to accurate charge estimation since it directly influences the speed–density charge mass calculation [1, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…The research [6] proposed an air mass flow estimator design with model bias correction for a turbocharged diesel engine by off-line calculation. An in-cylinder air mass observer was implemented in [7], which combined the feedforward neural static model and a linear parameter varying (LPV) polytopic observer. Some air charge observers have been reported in [8,9] on the SI engine and the experimental results showed that the input estimation techniques could enhance the control performance.…”
Section: Introductionmentioning
confidence: 99%
“…Let us consider the system investigated in [2], the airpath of a turbocharged Spark Ignition engine. Here, we focus on the subsystem from which the air flow trapped into the cylinders can be estimated.…”
Section: A Examplementioning
confidence: 99%
“…,z k 2 . l n 2 : the Hilbert space of right-sided square summable real vector sequences of vectors of dimension n. l n ∞ : the Banach space of right-sided bounded sequences z of real vectors of dimension n. z 2 …”
mentioning
confidence: 99%